Moments of Despair: Suicide, Divorce, and Debt in Civil War Era North Carolina - Silkenat, David (The University of North Carolina Press, 2011)
During the Civil War era, black and white North Carolinians were forced to fundamentally reinterpret the morality of suicide, divorce, and debt as these experiences became pressing issues throughout the region and nation. InMoments of Despair, David Silkenat explores these shifting sentiments.Antebellum white North Carolinians stigmatized suicide, divorce, and debt, but the Civil War undermined these entrenched attitudes, forcing a reinterpretation of these issues in a new social, cultural, and economic context in which they were increasingly untethered from social expectations. Black North Carolinians, for their part, used emancipation to lay the groundwork for new bonds of community and their own interpretation of social frameworks. Silkenat argues that North Carolinians' attitudes differed from those of people outside the South in two respects. First, attitudes toward these cultural practices changed more abruptly and rapidly in the South than in the rest of America, and second, the practices were interpreted through a prism of race. Drawing upon a robust and diverse body of sources, including insane asylum records, divorce petitions, bankruptcy filings, diaries, and personal correspondence, this innovative study describes a society turned upside down as a consequence of a devastating war.